Al0.2Ga0.8As Solar Cells Monolithically Grown on Si and GaAs by MBE for III-V/Si Tandem Dual-junction Applications. (August 2016) - Onno, Arthur; Wu, Jiang; Jiang, Qi; Chen, Siming; Tang, Mingchu; Maidaniuk, Yurii; Benamara, Mourad; Mazur, Yuriy I.; Salamo, Gregory J.; Harder, Nils-Peter; Oberbeck, Lars; Liu, Huiyun
Abstract: Al0.2 Ga0.8 As photovoltaic solar cells have been monolithically grown on silicon substrates by Molecular Beam Epitaxy. Due to the 4% lattice mismatch between AlGaAs and Si, Threading Dislocations (TDs) nucleate at the III-V/Si interface and propagate to the active region of the cells where they act as recombination centers, reducing the performances of the devices. In order to reduce the Threading Dislocation Density (TDD) in the active layers of the cells, InAlAs Strained Layer Superlattice (SLS) Dislocation Filter Layers (DFLs) have been used. For one of the samples, in-situ Thermal Cycle Annealing (TCA) steps have additionally been performed during growth. For comparison purposes, reference Al0.2 Ga0.8 As solar cells have been grown lattice-matched on GaAs. For the sample grown on Si without TCA, the TDD has been reduced from over 7×10 9 cm -2 at the III-V/Si interface to 3×10 7 cm -2 in the base of the cells. With TCA, the TDD has been reduced throughout the sample from over 3×10 9 cm -2 in the initial epilayers to 8(±2)×10 6 cm -2 in the base of the cells. For the best devices, the Voc improves from 833mV on Si without TCA to 895mV using TCA, compared with 1070mV for the reference sample grown lattice-matched on GaAs. Similarly the fill factor improves from 73.7% on Si without TCA to 74.8% using TCA, compared with 78.4% on GaAs. The high bandgap-voltage offset obtained both on Si and GaAs indicates a non-optimal bulk AlGaAs material quality due to non-ideal growth conditions.